Functional and comparative genomics reveals conserved noncoding sequences in the nitrogen‐fixing clade. Issue 2 (21st February 2022) - Pereira, Wendell J.; Knaack, Sara; Chakraborty, Sanhita; Conde, Daniel; Folk, Ryan A.; Triozzi, Paolo M.; Balmant, Kelly M.; Dervinis, Christopher; Schmidt, Henry W.; Ané, Jean‐Michel; Roy, Sushmita; Kirst, Matias
Summary: Nitrogen is one of the most inaccessible plant nutrients, but certain species have overcome this limitation by establishing symbiotic interactions with nitrogen‐fixing bacteria in the root nodule. This root–nodule symbiosis (RNS) is restricted to species within a single clade of angiosperms, suggesting a critical, but undetermined, evolutionary event at the base of this clade. To identify putative regulatory sequences implicated in the evolution of RNS, we evaluated the genomes of 25 species capable of nodulation and identified 3091 conserved noncoding sequences (CNS) in the nitrogen‐fixing clade (NFC). We show that the chromatin accessibility of 452 CNS correlates significantly with the regulation of genes responding to lipochitooligosaccharides in Medicago truncatula . These included 38 CNS in proximity to 19 known genes involved in RNS. Five such regions are upstream of MtCRE1, Cytokinin Response Element 1, required to activate a suite of downstream transcription factors necessary for nodulation in M .  truncatula . Genetic complementation of an Mtcre1 mutant showed a significant decrease of nodulation in the absence of the five CNS, when they are driving the expression of a functional copy of MtCRE1 . CNS identified in the NFC may harbor elements required for the regulation of genes controlling RNS in M .  truncatula .